PERLINDUNGAN HUKUM BAGI PEMILIK MEREK TERKENAL DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Matulessy, Maria Fransina; Hulman Panjaitan; Andrew Betlehn (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The prominence of a brand can trigger acts of brand violations both on a national and international scale. The use of brands especially well-known marks without the permission of the brand owner is very detrimental to the actual registered brand owner. At this time many products or counterfeit goods are used and circulating in the market to gain economic benefits, even these products boldly record some aspects that have similarities such as visuals, shapes, colors, names and even logos of the original brand. So that the main problem in this thesis is the equation basically to the brand in toothpaste between XXXX and PT. XXXX. resulted in a loss to one of the parties. Therefore, the need for Legal Protection for Owners of Famous Brands Related to Equality Is Basically Reviewed From the Law of the Republic of Indonesia Number 20 of 2016. The research method used by the author in the preparation of this study is a type of normative legal research, namely legal research that prioritizes secondary data, namely data obtained from library materials related to the topics studied in the form of books and Law No. 20 of 2016 on Brands and Geographical Indications. And this research is conducted by reviewing the contents of the Supreme Court Decision No. XXX K / Pdt. Sus-HKI / 2021. The results of this thesis show that the legal protection of the brand is given to the owner of the brand that has been registered first automatically in the Directorate General of Intellectual Property Rights as in accordance with the brand registration system embraced in Indonesia, namely the first to file system.